The political system in the Umayyad era - Fadel بتول عباس; Mal Allah أ. د نضال مؤيد (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The research dealt with the study of the political system in the Umayyad era and the efforts made by the Umayyads in order to reach a method by which the caliphate would be transferred in a proper manner, as well as the Umayyads’ endeavor to establish an Umayyad state in which no one would dispute them. Opposition and internal strife in order to establish a stable Umayyad state.